Development of a speed breeding protocol with flowering gene investigation in pepper (Capsicum annuum) - Choi, Hayoung; Back, Seungki; Kim, Geon Woo; Lee, Kyeongseok; Venkatesh, Jelli; Lee, Hyo Beom; Kwon, Jin-Kyung; Kang, Byoung-Cheorl (Frontiers in Plant Science, 2023)
Pepper (Capsicum spp.) is a vegetable and spice crop in the Solanaceae family with many nutritional benefits for human health. During several decades, horticultural traits, including disease resistance, yield, and fruit quality, have been improved through conventional breeding methods. Nevertheless, cultivar development is a time-consuming process because of the long generation time of pepper. Recently, speed breeding has been introduced as a solution for shorting the breeding cycle in long-day or day-neutral field crops, but there have been only a few studies on speed breeding in vegetable crops. In this study, a speed breeding protocol for pepper was developed by controlling the photoperiod and light quality. Under the condition of a low red (R) to far-red (FR) ratio of 0.3 with an extended photoperiod (Epp) of 20 h (95±0 DAT), the time to first harvest was shortened by 75 days after transplant (DAT) compared to that of the control treatment (170±2 DAT), suggesting that Epp with FR light is an essential factor for flowering in pepper. In addition, we established the speed breeding system in a greenhouse with a 20 h photoperiod and a 3.8 R:FR ratio and promoted the breeding cycle of C. annuum for 110 days from seed to seed. To explain the accelerated flowering response to the Epp and supplemented FR light, genome-wide association study (GWAS) and gene expression analysis were performed. As a result of the GWAS, we identified a new flowering gene locus for pepper and suggested four candidate genes for flowering (APETALA2 (AP2), WUSCHEL-RELATED HOMEOBOX4 (WOX4), FLOWERING LOCUS T (FT), and GIGANTEA (GI)). Through expression analysis with the candidate genes, it appeared that Epp and FR induced flowering by up-regulating the flowering-promoting gene GI and down-regulating FT. The results demonstrate the effect of a combination of Epp and FR light by genetic analysis of flowering gene expression. This is the first study that verifies gene expression patterns associated with the flowering responses of pepper in a speed breeding system. Overall, this study demonstrates that speed breeding can shorten the breeding cycle and accelerate genetic research in pepper through reduced generation time.